The Randomized AMBORA Trial: Impact of Pharmacological/Pharmaceutical Care on Medication Safety and Patient-Reported Outcomes During Treatment With New Oral Anticancer Agents. Issue 18 (20th June 2021) - Dürr, Pauline; Schlichtig, Katja; Kelz, Carolin; Deutsch, Birgit; Maas, Renke; Eckart, Michael J.; Wilke, Jochen; Wagner, Harald; Wolff, Kerstin; Preuß, Caroline; Brückl, Valeska; Meidenbauer, Norbert; et al.
Abstract : PURPOSE: Oral anticancer drugs (eg, kinase inhibitors) play an important role in cancer therapy. However, considerable challenges regarding medication safety of oral anticancer drugs have been reported. Randomized, controlled, multicenter studies on the impact of intensified clinical pharmacological/pharmaceutical care on patient safety and patient treatment perception are lacking. METHODS: Patients were eligible for the randomized, multicenter AMBORA study, if they were newly started on any of the oral anticancer drugs approved in 2001 or later without restriction to certain tumor entities. Patients were randomly assigned to receive either standard of care (control group) or an additional, intensified clinical pharmacological/pharmaceutical care, which included medication management and structured patient counseling, over a period of 12 weeks (intervention group). Primary end points were the number of antitumor drug–related problems (ie, side effects and unresolved medication errors) and patient treatment satisfaction with the oral anticancer therapy after 12 weeks measured with the Treatment Satisfaction Questionnaire for Medication, category convenience. RESULTS: Two hundred two patients were included. Antitumor drug–related problems were significantly lower in the intervention compared with the control group (3.85 v 5.81 [mean], P < .001). Patient treatment satisfaction was higher in the intervention group (Treatment Satisfaction Questionnaire for Medication, convenience; 91.6 v 74.4 [mean], P < .001). The hazard ratio for the combined end point of severe side effects (Common Terminology Criteria for Adverse Events ≥ 3), treatment discontinuation, unscheduled hospital admission, and death was 0.48 (95% CI, 0.32 to 0.71, P < .001) in favor of the intervention group. CONCLUSION: Treatment with oral anticancer drugs is associated with a broad range of medication errors and side effects. An intensified clinical pharmacological/pharmaceutical care has considerable, positive effects on the number of medication errors, patient treatment perception, and severe side effects.